Identification of the Implementation Level of the Covid-19 Protocol in Service Providers Building (Case Study of Palu City Area) - Andi Asnudin; Anisa Dwi Syafira (Lowland Technology International, 2022)
ABSTRACT Construction projects themselves are one of the aspects affected by Covid-19. Therefore, a rule is required to be used as a protocol in the implementation of work in the field of construction which in this case is the Instruction of the Minister of PUPR No.2 of 2020. This study aims to find out the level of Implementation of Covid Protocol in Construction Service Providers that located in Palu city . Technical research uses questionnaires based on samples from several contractors who are running projects in Palu City. Questionnaires that have been distributed are then analyzed using percentage and RRI methods. The results showed that the level of implementation of the Covid-19 protocol on construction projects based on sub indicators with the application rate is "Highly Applied" and the highest RRI value is 0.870 to the lowest RRI value of 0.711. Some of these indicators are (1) Allocating costs for cleaning facilities (0.870), (2) Dividing work locations by type of work (0.863), (3) Preparing facilities and infrastructure for washing hands, keeping distance, and avoiding crowds for employees (0.859), ( 4) Provide hand washing facilities with soap, disinfectant, hand sanitizer, tissue, and masks in the office and project field. (0.859), (5) Forbidding someone who is sick with an indication of a temperature > 38 degrees Celsius to go to the project site (0.856), (6) Establishing a Covid Prevention Task Force (0.856), (7) Reporting to PPK if positive workers are found and/Patients Under Supervision (PDP), and provide advice to temporarily suspend project activities (0.852), (8) Conduct socialization and education on the Covid protocol (0.844), (9) Conduct socialization related to the Covid 19 prevention protocol in construction projects (0.833) , and (10) Implementing regulations related to Covid prevention protocols on construction projects (0.833)